EFFECTIVENESS OF THE IMPLEMENTATION OF MEANINGFUL INSTRUCTIONAL DESIGN LEARNING MODEL IN IMPROVING INTEREST AND STUDENT LEARNING OUTCOMES OF PHYSICS IN CLASS X SENIOR HIGH SCHOOL - Sulistia Budi (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2019)
The purpose of this action research is to increase the interest and learning outcomes of physics students with the implemention of the Meaningful Instructional Design Model (MID). The influence of internal factors experienced by students in learning physics include difficulties in understanding the material and solving the questions correctly, so that students' learning interest is low. Meaningful Instructionnal Design Model includes a learning model that prioritizes learning meaningfulness, which should be able to increase students' interest and learning outcomes. This research is a classroom action research conducted in two cycles. The subjects of this study were students of class XI MIPA4, SMA Negeri 1 Pekanbaru. The research instrument used observation sheets for interest and test sheets for physics learning outcomes in fluid material. Data is analyzed descriptively in percentage representation. The results of the research obtained the interest of students in physics learning, experiencing an increase from cycle I to cycle II. The same thing for learning outcomes of physics students also increased from cycle I to cycle II, with the average results obtained very good category. Thus the implementation of the Meaningful Instructionnal Design (MID) model is effective in increasing interest and learning outcomes of students of class XI MIPA4 SMA Negeri 1 Pekanbaru, in learning fluid material.